Evangelical eucharistic thought in the Church of England - Cocksworth, Christopher J. (Cambridge University Press, 1993)
This book studies the way the central act of Christian worship (variously known as the Eucharist, the Lord's Supper, the Holy Communion, and the Mass) has been treated in the thought and practice of the Evangelical tradition in the Church of England. Evangelicals are not associated with an emphasis on the Eucharist, and Dr. Cocksworth's study is important and potentially very influential because it demonstrates that--at its times of strength--the Evangelical tradition has held the Eucharist in the highest regard